Eucharis amazonica Amazon Lily, Eucharist Lily: FPS198/FP198, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the Amazon lily (Eucharis amazonica), a perennial, herbaceous plant known for its glossy green leaves and fragrant white flowers. It discusses the plant’s characteristics, including its moderate growth rate, semi-evergreen leaves, and winter flowering. The document also covers the plant’s preferred growing conditions, such as shade and rich, moist organic matter, and notes its moderate pest resistance. Additionally, it highlights the plant’s uses as a ground cover or accent and mentions its propagation by division. Potential problems like caterpillars, spider mites, and bulb mites are also addressed. Original publication date September 1999.